Design and Experimental Study of Composite Cross Arm Tension Release Device - Wenbin Li; Junzhe Lin; Xinlong Wang; Yanlin Li; Xiaolei Zhang; Junfeng Bai; Dehong Wang (Advances in Civil Engineering)
The composite cross arm tower exhibits excellent electrical performance, which contributes to a reduction in the width of transmission line corridors, minimizes the use of steel in transmission towers, and mitigates issues such as wind bias tripping. This functionality supports the low-carbon design of overhead transmission lines, emphasizing the importance of quality and efficiency. However, the elimination of the suspension insulator string in composite cross arm linear towers leads to significant longitudinal unbalanced tension during adverse conditions such as conductor line breaks or ice accumulation. This excessive force can cause local damage or even collapse of the tower due to overstressing of the diagonal members. To address this challenge, we propose a new composite cross arm structure incorporating a C-shaped rotating device designed to alleviate unbalanced tension in composite cross arm towers. The mechanical performance of this structure was assessed through both full-scale tests and finite element simulations, confirming that the structure operates within an elastic range. The rotation axis was identified as the weakest point, with stress peaks remaining significantly below the yield strength, thereby indicating a high level of safety and a considerable safety margin. The C-shaped rotating device features a 380 mm range of motion and effectively releases unbalanced tension during actual line operations. Overall, the new composite cross arm structure with the C-shaped rotating device demonstrates favorable mechanical properties.